Działalność Państwowego Banku Rolnego w Generalnej Guberni - Kłusek, Mirosław (Annales. Etyka w Życiu Gospodarczym, 2013)
In this article we try to estimate the activity of the banking institution in the General Government which used the pre-war apparatus of The National Bank of Agriculture. The bank was one ofthe largest banks realising the aim delineated by the government of the Second Polish Republic, such as the support of agricultural reform in the mid-war period. German authorities in the General Government used assets of the bank for other tasks. They were eager to use The National Bank of Agriculture and the Polish staff employed in the bank in order to liquidate fast and effectively the mid-war assets of the bank. Leaving The National Bank of Agriculture was also good for Polish staff in the bank. Raising pre-war debts was the only way to guarantee salary and pensions forthe employees of the National Bank of Agriculture and taking care of them in the hard life of occupation. The activity of the National Bank of Agriculture in the General Government was also profitable for a part of debtors as they could pay the pre-war credits earlier. One reason for agriculture farms becoming poorer and even ruined was war actions and the occupation. However, the farmers could save money and gather capital more easily. When they often sold food in secret, they got a large amount of money. In many cases, paying back the pre-war debt was the only reasonable way of getting rid of almost valueless money, although it did not mean that it was done without doubts. In the beginning, many people claimed that they would give it back to whom they had borrowed from. However, after a while the patriotism of farmers who were debtors was overcome by the willingness to have no debts and leave children in a new condition. The period of German occupation and increasing inflation was used for paying back the debt in valueless money, not only by farmers but also by owners of the large mansions such as Earl Adam Branicki.